2014
DOI: 10.1117/12.2055874
|View full text |Cite
|
Sign up to set email alerts
|

Preserving accurate figures in coating and bonding mirrors for lightweight x-ray telescopes

Abstract: Lightweight, high-resolution, high throughput optics for x-ray astronomy requires fabrication and integration of thin mirrors segments with arc-second precision. In this paper, we present results on our effort leading to the most recent two test modules achieving the intermediate goal of 10 arc-second resolution. We will address issues of coating and bonding thin glass mirrors with negligible distortion. Annealing of sputtered high-density metallic films was found to be sufficiently accurate. We will present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…An important advantage of the SGO technique is the light weight of the mirrors since their density is only ∼2.5 g/cm 3 . Thermally slumped glass optics have been used for the NuSTAR mission, whose telescopes contain 133 shells of thin glasses [21,22]. During the slumping process, the glass is slumped very slowly onto the convex surface of the mandrel to assume its shape [23].…”
Section: -5mentioning
confidence: 99%
“…An important advantage of the SGO technique is the light weight of the mirrors since their density is only ∼2.5 g/cm 3 . Thermally slumped glass optics have been used for the NuSTAR mission, whose telescopes contain 133 shells of thin glasses [21,22]. During the slumping process, the glass is slumped very slowly onto the convex surface of the mandrel to assume its shape [23].…”
Section: -5mentioning
confidence: 99%
“…Moreover, the resulting stress distribution, thereby distortion, is not reproducible, making it difficult to understand and eliminate. We have found that the most effective method of reducing coating stress is a thermal annealing process following the MS or ALD process [26,27]. All mirrors used in our current development have been coated and annealed this way.…”
Section: Coatingmentioning
confidence: 99%
“…For example, on a glass mirror segment with a radius of 250 mm, a length of 200 mm, a angular width of 30°, and a thickness of 0.4 mm, the coating distortion is about 3 µm PV for every 10 nm of Ir deposited. The coated film can be annealed to reduce the internal stress and therefore the mirror's figure can be improved 20,21 . Thermal annealing was shown to be very effective even at temperature as low as 350°C.…”
Section: Adjustment Of Techniques For Silicon Substratesmentioning
confidence: 99%